Evaluation of healing dynamics in root coverage therapy: A systematic review of digital technologies - Lory Abrahamian; Erika Brancacci; Ricardo Palacios-Bañuelos (Elsevier, 2024)
This review highlights the use of optical scanning-based digital technologies in assessing volumetric changes following root coverage therapy. A comprehensive search was conducted in different databases to identify interventional studies reporting on volumetric changes after root coverage surgery using various approaches. 12 articles from 10 studies meeting the inclusion criteria were included in the qualitative synthesis. The documented volumetric outcomes encompassed changes in volume (Vol) measured in mm³, mean distance between surfaces (ΔD) in mm, and linear dimensional changes (LD) in mm. A notable divergence was observed in determining the Region of Interest (ROI). The observed variability in methodologies and outcomes underscores the necessity for standardized approaches and reporting guidelines, enabling volumetric comparisons across different studies and treatments.